ASPARTATE AMINOTRANSFERASE PLATELET RATIO INDEX AS A NON-INVASIVE PREDICTOR FOR ESOPHAGEAL VARICES - Raza, Syed Hassan; Ahmad, Imran; Habib, Aamir; Humayaun, Zill -e-; Yousaf, Muhammad Ali; Yousaf, Muhammad Javad (Pakistan Armed Forces Medical Journal, 2019)
Objective: To determine the diagnostic accuracy of Aspartate Aminotransferase Platelet Ratio Index (APRI) as a predictor for esophageal varices.Study Design: Cross-sectional validation study.Place and Duration of Study: Department of Medicine, PNS Shifa Hospital Karachi, from Oct 2015 to Sep 2016.Patients and Methods: One hundred and thirty five patients were enrolled in this study. Patients included in thisstudy belonged to both genders, and were aged between 18 to 80 years. Cirrhosis was detected by Ultrasonography. Platelet count and Serum Aspartate Aminotransferase (AST) levels were performed in pathology laboratory. APRI ratio was calculated by using the formula AST (times above upper limit of normal)/ platelets x(109/L) x 100. For each patient APRI was determined with a cutoff value of 1.3. Sensitivity, specificity, accuracy, positive predictive value and negative predictive value of APRI were calculated by comparing it with upper gastrointestinal endoscopy as a gold-standard.Results: In this cross sectional validation study, 27.4% (n=37) were aged between 18-40 years, 52.6% (n=71) were aged between 41 to 60 years and 27% (n=20) were aged between 61 to 80 years of age respectively, and mean ± SD was calculated as 48.6 ± 14.3. Amongst the total, 63.7% (n=86) were males whereas 36.3% (n=49) were females. The diagnostic accuracy of APRI was determined, considering endoscopy as gold standard, 65 % (n=65) were true positive, 35% (n=35) were false positive, 51.4% (n=18) were false negative and 48.57% (n=17) were true negative. Sensitivity, specificity and accuracy of APRI were 78.3%, 32.7% and 60.7%, respectively. Positive predictive value, negative predictive and diagnostic accuracy of APRI was 65.0%, 48.5% and 60.7% respectively.Conclusion: Our study results signify that APRI is an unsuitable replacement for endoscopy and cannot help in the screening of esophageal varices among cirrhotics because of low specificity and negative predictive value hence proved that we need further evaluation/trials to use APRI as a screening test in our domestic population.